5x(a-6b+5c)-2x(b-c)=

Simple and best practice solution for 5x(a-6b+5c)-2x(b-c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x(a-6b+5c)-2x(b-c)= equation:


Simplifying
5x(a + -6b + 5c) + -2x(b + -1c) = 0
(a * 5x + -6b * 5x + 5c * 5x) + -2x(b + -1c) = 0
(5ax + -30bx + 25cx) + -2x(b + -1c) = 0
5ax + -30bx + 25cx + (b * -2x + -1c * -2x) = 0
5ax + -30bx + 25cx + (-2bx + 2cx) = 0

Reorder the terms:
5ax + -30bx + -2bx + 25cx + 2cx = 0

Combine like terms: -30bx + -2bx = -32bx
5ax + -32bx + 25cx + 2cx = 0

Combine like terms: 25cx + 2cx = 27cx
5ax + -32bx + 27cx = 0

Solving
5ax + -32bx + 27cx = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '32bx' to each side of the equation.
5ax + -32bx + 32bx + 27cx = 0 + 32bx

Combine like terms: -32bx + 32bx = 0
5ax + 0 + 27cx = 0 + 32bx
5ax + 27cx = 0 + 32bx
Remove the zero:
5ax + 27cx = 32bx

Add '-27cx' to each side of the equation.
5ax + 27cx + -27cx = 32bx + -27cx

Combine like terms: 27cx + -27cx = 0
5ax + 0 = 32bx + -27cx
5ax = 32bx + -27cx

Divide each side by '5x'.
a = 6.4b + -5.4c

Simplifying
a = 6.4b + -5.4c

See similar equations:

| 64x^2+105x+56=0 | | 1/2-x*1/2=1/8 | | 12-x=1/8 | | 14.2=7x-3.3 | | 1/2-x*51/2=1/8 | | 3xw*4w= | | 7c*4e= | | 1.5=(x-90)/15/3 | | 0=-125+20x+0.44x^2 | | 1.5=(x-90)/15/√(9) | | 8=15t-4.9t^2 | | 7x^2+9x+363=0 | | 6x-2(4y+x)= | | 3.2=28.8-8u | | 2x+4y+.125z=75 | | 10.1=5v-2.4 | | 200/86 | | 481.9/0.61 | | 2x-4x=100 | | 15x-4=3x | | 29.7-8y=4.1 | | f(3k+2)=54k^3+18k^2+12k | | 4x^3+6x^2-24x+1=0.5 | | 14x+11=-1+16x | | 14x+11=-1+16 | | 50-25i/25 | | e^3-7x=1881 | | x+134+x+64=180 | | 6b-7(2b-8)= | | 5ln(5x+6)=26 | | 6b-7-(2b-8)= | | g(x)=[log(4X^3-3X^2)] |

Equations solver categories